PENGELOLAAN TANAH WAKAF PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SOLOK - Arnal Yanuardi; Yeni M (Jurnal Public Administration, Business and Rural Development Planning, 2020)
The results of the observations illustrate that the existence of waqf in Kubung District is only used for the construction of mosques, prayer rooms, schools, and social institutions in the form of orphanages and nursing homes, while in the implementation of registration of land waqf from wakif is through the Office of Religious Affairs in Kubung District and forwarded to the Head of Bimas Islam at the Office of the Ministry of Religion of Solok Regency. The forms of Waqf Land Management in Kubung District, Solok Regency are:1) Problems in the management of Waqf Land in Kubung District, Solok Regency. The problem of waqf management in Kubung District is stillthe existence of waqf land that has not been certified due to constraints onNazhir in the management of land certificates that do not exist, this is because Nazhir does not carry out his duties in accordance with existing laws. The practice of productive waqf it self has not been carried out because it is constrained by nazhir who does not know about productive waqf, 2) The strategy for managing waqf land in Kubung sub-district, Solok district, is only intended for the construction of worship facilities, so the results achieved from waqf land that are currently managed are not maximized because has not been managed productively due to Nazhir's knowledge of productive waqf so that the managed waqf land has not been able to prosper the people in the area around the district of Kubung